The Alexander inheritance - Flint, Eric; Huff, Gorg; Goodlett, Paula (Flint, Eric. Queen of the sea, 2017)
Catapulted two thousand years into the past by a cosmic force, the crew and passengers of a cruise ship struggle to survive in Egypt during the war-torn years of the Ptolemaic era.